Rate of action of schistosomicides in mice infected with Schistosoma mansoni - Naftale Katz; Emmanuel Pinto Dias; Cecilia Pereira de Souza; John I. Bruce; Gerald C. Coles (Revista da Sociedade Brasileira de Medicina Tropical, 1989)
Mice infected with adult Schistosoma mansoni were dosed with a single oral dose of 125 or 250 mg/kg oltipraz, 50 or 100 mg/kg oxamniquine, or 200 or 400 mg/kg praziquantel. The mortality rate of worms and oogram changes were determined between 1 and 16 weeks after dosing. The time required between dosing and postmortem to obtain maximum effectiveness was 1 week for praziquantel, 2 weeks for oxamniquine and 8 weeks for oltipraz. Changes in oograms persisted throughout most of the experiment, although relapse has been observed at the 4th week on.